The relationship between physical activity, body mass index and academic performance of Iraqi graduate students in Malaysia - Falah, Dhubyan Jihad; Yusof, Aminuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This study examined the relationship between physical activity (PA), body mass index (BMI) and academic performance of Iraqi graduate students in Universiti Putra Malaysia. Participants of this study were 200 graduate students (male= 125, female= 75) in UPM. Data were collected using the International Physical Activity Questionnaire (IPAQ) short version to measure the level of physical activity of participants. Body mass index (BMI) was measured by the equation of BMI, which depends on weight and the square of height for the participants. Grade point average (GPA) was used as a measure for academic performance. There was a positive and significant relationship between physical activity and academic performance (r=0.235, p<0.01). However, a negative relationship was found for body fat and weight (BMI scores) and academic performance (r=-0.202, p<0.01). It was concluded that there is a strong positive association between (PA) and academic performance, and a significant relationship between (BMI) score and academic performance among Iraqi graduate students at UPM.